Evaluación de un tratamiento biotecnológico por medio de Pleurotus ostreatus, y biomasa vegetal para el tratamiento de aguas sintéticas con un contenido de fenoles. (2023)
A treatment will be studied on this article, involving Pleurotus ostreatus, and taking advantage on the enzymes it contains or produce the fungi who contribute to phenol degradation. The treatment researched on this article will produce a series of bio-sheets, using the fungi and a vegetable matrix; scourer. Having complete the bio-sheets, they were put to test in a controlled medium containing pure phenol crystals, diluted in distilled water, decreasing the concentration from 10mg/L to 0.97mg/L.